Function promotion of SO42−/Al2O3–SnO2 catalyst for biodiesel production from sewage sludge. (March 2020) - Zhang, Rongyan; Zhu, Fenfen; Dong, Yi; Wu, Xuemin; Sun, Yihe; Zhang, Dongrui; Zhang, Tao; Han, Meiling
Abstract: Catalysts are critical materials for biodiesel production using sewage sludge feedstock. In this research, different SO4 2− /Al2 O3 –SnO2 catalysts were prepared and characterized. The catalysts prepared at different conditions were characterized through Brunauer-Emmett-Teller (BET), X-ray diffraction (XRD), NH3 -temperature-programmed desorption (NH3 -TPD), NH3 adsorption FT-IR, and TGA. Then, esterification/transesterification reaction was performed with the lipid extracted from sewage sludge to verify the activity of these catalysts. Results showed that the catalysts with n(Al):n(Sn) = 1:10 prepared by 79 wt% H2 SO4 possessed the best physical properties with a large number of active catalytic sites, which led to the biodiesel yield of 73.3% (based on dried extracted crude fat) under the optimized reaction conditions at 130 °C as reaction temperature, 0.8 g as catalyst loading for lipids extracted from 10 g freeze-dried sludge, 4 h as reaction time. Catalysts characterization results showed that acidity, acid sites and Al/Sn molar ratio play an important role in the activity of catalysts. The thermal properties showed that 450 °C was the suitable calcination temperature for catalyst preparation. The optimized SO4 2− /Al2 O3 –SnO2 catalyst in this research will have a bright future in the field of sludge production of biodiesel. Graphical abstract: Image 1 Highlights: SO4 2− /Al2 O3 –SnO2 can get 73.3% productivity of biodiesel from lipids in sewage sludge. The best preparation conditions:n(Al):n(Sn) = 1:10, 79 wt% H2 SO4 and calcined at 450 °C. Acidity, acid sites and Al/Sn molar ratio are important for SO4 2− /Al2 O3 –SnO2 activity.